24. THE ANALGESIC EFFECT AND IMPROVEMENT OF RADICULAR SYNDROME USING SCALP ACUPUNCTURE COMBINED WITH ELECTROACUPUNCTURE (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the analgesic effect and improvement of radicular syndrome in patients with sciatica using scalp acupuncture combined with electroacupuncture.Subjects and Methods: This was a controlled clinical intervention study conducted on 70 patients with sciatica characterized by liver and kidney deficiency combined with windcold-damp syndrome, who were treated as inpatients at Lao Cai Traditional Medicine Hospital.The patients were divided into two groups: the study group treated with scalp acupuncture combined with electroacupuncture, and the control group treated with electroacupuncture alone, over a period of 20 days.Results: After treatment, the study group showed a better reduction in VAS pain scores compared to the control group (1.51 ± 0.70 and 1.83 ± 0.57, respectively). The Lasegue test results improved more significantly in the study group than in the control group (78.6 ± 7.1 and 75 ± 6.37, respectively). Additionally, in the study group, 28.6% of patients reported complete relief from numbness and 71.4% reported reduced numbness, which was higher than in the control group (20% and 57.1%). These differences were statistically significant (p
Keywords: Scalp acupuncture; sciatica